Space, density and extra‐pair matings have opposing impacts on male and female reproductive success. Issue 2 (9th March 2020) - Lerch, Brian A.; Dautel, Kimberly A.; Brewer, Sharee; Liang, Alan; Siewe, Nourridine; Flanagan, Sarah
Abstract: Many territorial species have a mating system characterized by males establishing home ranges in the breeding grounds prior to females, resulting in males competing for territories and females choosing a mate upon their arrival. It remains unknown, however, how the outcomes of decisions surrounding territory establishment and mate choice are influenced by the spatial configuration of the breeding grounds. We use a spatially explicit, individual‐based model to investigate the sex‐specific effects of these decisions on reproductive success. In our model, males that arrive earlier obtain higher quality territories and improve their chances for extra‐pair copulations. Females can choose their mate to maximize the quality of the male or to attempt to minimize the density of other females near their nesting site to avoid competition. Females therefore face a tradeoff between high‐density regions around high‐quality males and low‐quality males in areas of low competition. Our model predicts a negative correlation between male and female reproductive success under a wide range of conditions when the majority of the territories are on the margins of the breeding area. Most notably, this sexual conflict arises as an edge effect suggesting that fragmentation of breeding habitats could impact the consequences of mate choice in many species with territorial breeding habits. Abstract : The role that spatial structure plays for determining reproductive outcomes of territorial breeders has been surprisingly understudied. Here, we show that an edge effect leads to a negative correlation between male and female reproductive success.